Empowering Sustainability and Consumer Satisfaction on Electric Vehicles Among Young Adults in Sulthan Battery: A Review - K. Thamarai Selvi; Sterina A.S. (International Journal of Electrical Machine Analysis and Design, 2023)
Electric vehicles are extremely eco-friendly while they require a small amount of fossil fuels (petrol or diesel), have fewer moving parts that are easier to maintain, and have low running costs. This vehicle is envisioned as a replacement for today’s automobiles. It can be used to address concerns such as pollution, global warming, natural resource depletion, and so on. The electric car concept offers a clear-cut solution to the environmental problems of gasoline-powered automobiles. This study is conducted to determine how people feel about electric automobiles. The goal is to reduce vehicular pollution by switching to electric vehicles. This study focuses on consumer satisfaction of electric vehicles attitude of students of Nilgiri College of Arts and Science, Thaloor. The project commences with fixing the objective then samples were collected accordingly. A total of 300 samples from the community were taken, and the results of the analyses were then obtained. The project's goals were established at the outset, and they have been met. This study conclude that majority of students are interested to prefer electric vehicles. Almost all the responders in the present study are men. The institute play an important role for promoting entrepreneurship and develop their ideas. Hence the study can be concluded that students of Nilgiri College have a positive attitude towards entrepreneurship.
Keywords: ICE engine; Plug-in hybrid electric vehicles; automobile Industries; consumer satisfaction; extraction method